Imágenes de páginas
PDF
EPUB

CHAPTER III.

TRIGONOMETRIO FUNCTIONS OF TWO ANGLES.

42. Fundamental Formulæ. We now proceed to express the trigonometric functions of the sum and difference of two angles in terms of the trigonometric functions of the angles themselves.

The fundamental formulce first to be established are the following: sin (x + y)=sin x cos y + cosa siny

(1) cos (x + y) = cos X COS Y — sin x siny

(2) sin (x - y) sin 3 cos Y - cos x siny.

(3) cos (x - y) = cos x cos y + sin x siny.

(4)

[ocr errors]

NOTE. – Here x and y are angles; so that (2 + y) and (x – y) are also angles.
Hence, sin (x + y) is the sine of an angle, and is not the same as sin x + siny.
Sin (x + y) is a single fraetion.
Sin x + sin y is the sum of two fractions.

43. To prove that sin (x + y)

sin x cos y + cos x sin y, and cos (x + y) = cos x cos y sin x sin y.

Let the angle AOB = x, and the angle BOC = y; then the angle AOC = x + y.

In OC, the bounding line of the angle (x + y), take any point P, and draw PD, PE, perpendicular to OA and OB, respectively; draw EH, EK, perpendicular to PD and 0A.

[ocr errors][merged small][merged small][merged small][merged small][merged small]

[merged small][merged small][merged small][merged small][merged small][merged small][merged small][merged small][merged small][merged small][merged small][merged small][merged small][ocr errors][merged small][merged small][merged small]

NOTE. — These two formulæ have been obtained by a construction in which x + y is an acute angle; but the proof is perfectly general, and applies to angles of any magnitude wbatever, by paying due regard to the algebraic signs. For example, Let AOB = x, as before, and BOC=Y;

B then AOC, measured in the positive direction, is the angle x + y.

In OC, take any point P, and draw PD, PE, perpendicular to OA and OB produced;

K D draw EH and EK perpendicular to PD and

A OA.

Tben, angle EOK = 180° — XC;

[blocks in formation]

=- sin (1800 — 2) cos (y - 1800) + cos (1800 – x) sin (y - 180°) = sin x cos y + cos x sin y.

(Art. 35)
OD OK + EH OK EH
GO8 (XC + y)

+
OP OP OP OP

[merged small][ocr errors]

* The introduced line OE is the only line in the figure which is at once a side of two right triangles (OEK and OEP) into which EK and OP enter. A similar remark applies to PE.

=cos (180° — x) cos (y - 180°) + sin (180° — 2) sin (y – 180°)

= cos X COBY - sin x bin y.

(Art. 35)

The student should notice that the words of the two proofs are very nearly the

same,

44. To prove that sin (x y) =

= sin x cosy – cos x sin y, and cos (x - y) = cos x cos y + sin x siny.

I

[ocr errors]

B
Let the angle AOB be denoted
by x, and COB by y; then the angle
X

E
AOC =X - y.
In OC take any point P*, and

P
draw PD, PE, perpendicular to
OA and OB respectively; draw
EH, EK, perpendicular to PD and o

K D
OA respectively.

Then the angle EPH = 90° — HEP=BEH = AOB = x.

A

=

[blocks in formation]

NOTE 1. – The sign in the expression of the sine is the same as it is in the angle expanded; in the cosine it is the opposite.

* P is taken in the line bounding the angle under consideration; i.e., AOC.

NOTE 2. - In this proof the angle x - y is acute; but the proof, like the one given in Art. 43, applies to angles of any magnitude whatever. For example,

Let AOB, measured in the positive direction, = x, and BOC = y. Then AOC = x - y

H In OC take any point P, and draw CPD, PE, perpendicular to OA and OB produced: draw EH, EK, perpendicu. lar to DP and AO produced. Then,

DKI
angle EPH = EOK = AOB = 360° – X,
and POE = 180° - y.

B
PD EK HP
sin (x - y) =

OP OP

[blocks in formation]

= sin (360° - x) cos (180° — y) - cos (360° — 2) sin (180° - Y)
= (- sin x)(- cox y) - cos X sin y

[merged small][merged small][merged small][merged small][merged small][merged small][ocr errors]

= - cos (360° — 2) cos (180° - y) - sin (360° — 2) sin (180° - y)

(- cos x)(- cos y) - (- sin x) sin y

= cos x cos y + sin x sin y.

NOTE 3. — The four fundamental formulæ just proved are very important, and must be committed to memory. It will be convenient to refer to them as the 'x, y' formulæ. From any one of them, all the others can be deduced in the following mapper :

Thus, from cos (x – y) to deduce sin (x+y). We have cos (x - y) = cos x cos y + sin x siny.

(1)

[ocr errors]

.

Substitute 90° — x for x in (1), and it becomes cos{90° — (x + y)}=cos (90° — «) cosy +sin (90° — «) sin y.

=
.. sin (a + y)=sinæ cosy + cos x sin

ny. (Art. 29)

The student should make the substitutions indicated below, and satisfy himself that the corresponding results follow:

From

66

sin (x + y) to deduce cos (x+y) substitute (90°+x) for x. cos (2 y)

(90° — 2) for x. cos (x+y) sin (x + y)

(90° + x) for x. sin (-y)

(90° — 2) for x. cos (a y)

- y for y.

6

[ocr errors]
[blocks in formation]
[ocr errors]

V22

sin 45o cos 30° cos 45o sin 30°

1 V3 1 1 V2

2 V3–1.

2 V2

V3+1. 2. Show that sin 75°=

22 V3 - 1

. 3. Show that cos 75o =

2 V2

V3+1. 4. Show that cos 15°=

22

5 5. If sin x= and COS Y

find sin (x + y) and cos (x - y).

63 56 Ans. and

65' 65 1

1 6. If sin x =

find sin (a + y) and

2' cos (-y).

Ans. 1, and

13

[ocr errors]

and cos y

[ocr errors]
« AnteriorContinuar »